CRYSTALLINITY AND PHASE COMPOUNDS IN POLYVINYL ALCOHOL-MONTMORILLONITE NANOCOMPOSITES THROUGH X-RAY DIFFRACTION AND OPTICAL MICROSCOPY - Papajani, Blerina; Como, Elvin; Hasimi, Albana; Lako, Alfred (LPPM Universitas Jambi, 2025)
The aim of this study was to analyse modern advancements in X-ray diffraction and optical microscopy to enhance the characterization of polyvinyl alcohol-montmorillonite (PVA-MMT) nanocomposites. The development of advanced nanocomposites has garnered significant attention due to their potential applications in various fields. Among these, polyvinyl alcohol reinforced with montmorillonite has emerged as a promising material owing to its enhanced mechanical and thermal properties. However, a thorough understanding of the crystallinity and phase compounds in these nanocomposites is essential for optimizing their performance and quality. To achieve this goal, recent studies on these techniques were systematically reviewed, and their effectiveness, advantages, and limitations were evaluated. The results demonstrated that digital holography, fluorescence microscopy, and confocal microscopy significantly improve the visualization of microstructural features and provide detailed 3D images and quantitative phase contrast. In situ X-ray diffraction allowed real-time monitoring of structural changes, while small-angle X-ray scattering provided detailed information about the size, shape, and distribution of nanostructured features. Synchrotron X-ray diffraction offered very high resolution and sensitivity, facilitating precise characterization of the nanocomposite’s properties. By integrating these advanced techniques, the study established a comprehensive framework for understanding the crystallinity and phase composition of PVA-MMT nanocomposites, paving the way for optimized material development.